Disastrous Mechanism of Water Discharge in Abandoned Gob above the Stope in Mining Extra-Thick Coal Seam. (4th March 2021) - Lin, Haixiao; Yang, Feng; Cao, Zhengzheng; Wang, Yue; Jiao, Xiaojian
Abstract : The Datong mining area is a typical double system coal seam mining area in China, where the Jurassic and Carboniferous coal seams are mined simultaneously. The upper Jurassic coal seam has been largely mined, leaving a large amount of gob area. Besides, a large amount of harmful water is accumulated. With the exploitation of the 3-5# extra-thick coal seam in the Carboniferous system, the scope of overburden damage is greatly increasing, and the mining fracture field is further developed. Once the mining-induced fractures connect with the overlying gob, it is easy to induce the water discharge disaster. With the mining geological conditions of the 8202 working face in the Tongxin coal mine as references, the disastrous mechanism of water discharge in the abandoned gob above the stope in the mining extra-thick coal seam is researched by numerical simulation with the UDEC numerical software, and the research results are obtained. The water in the overlying gob percolates through the mining-induced fractures in the higher key layer forming a "shower" seepage pattern. The water in the above gob converges in the key fracture channel, flowing into the working face. The seepage in the fractures in the high key stratum experiences the process of increase, decrease, and stabilization, related with the stretching and extrusion deformation between the high key stratum blocks. Compared with other fractures, the flow rates in the No.2 and No.4 fractures in the far field key lay are larger, because the fractures are in the tension state, forming the "saddle-shaped" flow pattern. The influencing distance of mining-induced seepage is about 80 m in front of the working face. The research results provide a guided reference for the prediction and prevention of water discharge disaster in an abandoned gob above the stope in a mining extra-thick coal seam.